Impact of the COVID-19 pandemic on the regional structure of international migration flows - Zvarych, Roman; Knysh, Liudmyla (Herald of Economics, 2021)
Introduction. International migration is a global process that has affected the populations of all countries and continents. Today, there is a new additional barrier for the world economy and for migrants – the COVID-19 pandemic, which has dramatically affected all forms of human mobility. The pandemic is the crisis of today and is the main problem of international migrants in combination with its consequences: threat to human life, global economic decline, declining migration flows, the crisis of medicine; and governments face additional challenges: finding solutions to compensate economic recession. In addition, international migration processes during the COVID-19 crisis are characterized by the following features: weak demand for labor, declining employment; strict travel restrictions; declining income. In addition to migrant-workers, other categories of international migrants, such as refugees and asylum seekers face problems. Wars, cataclysms, natural disasters and other catastrophes happen, but due to the pandemic, the recipient countries have stopped accepting migrants. This situation creates an economic threat to both migrant donor countries and migrant recipient countries and changes the regional structure of migration flows. Methods. The methodological basis of the study is a set of fundamental provisions of crisis theory, international migration theory, the world systems theory of migration, as well as modern concepts of post pandemic development. The solution of the set tasks was carried out by using a set of general scientific research methods: analysis of scientific literature, method of analogy and comparison, theoretical synthesis, classification, methodological generalization, economic and statistical analysis: correlation-regression analysis and the corresponding regression model, cluster analysis; expert assessments and scientific abstraction.The purpose of research – is to analyze the COVID-19 impact assessment on the recipients of international migration flows and define the impact of the pandemic on the regional structure of international migration flows.Results. The research proved that the consequence of the pandemic is a large-scale and radical blow to the global economy. In research defined the Corona Crisis concept in the theory of world crises. In research discover the COVID-19 impact assessment on the recipients of international migration flows. The research result suggests that the volume of international migration flows has a significant impact on the economy of the host country, but other factors influencing the change in GDP should be taken into account, that is fully explained by preventive measures against the COVID-19 pandemic and recipient country. In research defined the impact of the pandemic on the regional structure of international migration flows. Cluster analysis of the world regions classification by the volume of international migrants and the trend of their growth during the pandemic showed such results: clusters are distinguished by common features – the number of international migrants in the region in 2020 and trends of growth/decline of their volumes, which occurred during 2019-2020.Prospects. The results of the research discover the COVID-19 impact assessment on the recipients of international migration flows and define the impact of the pandemic on the regional structure of international migration flows. The prospect of further research is to apply the impact of the pandemic on the regional structure of international migration flows for the development of domestic migration policy.